The Role of Inflammation and Immune Activation on Circulating Endothelial Progenitor Cells in Chronic HIV Infection - Zhu, Ziang; Li, Tong; Chen, Jinya; Kumar, Jai; Kumar, Princy; Qin, Jing; Hadigan, Colleen; Sereti, Irini; Baker, Jason V.; Catalfamo, Marta (Frontiers in Immunology, 2021)
Endothelial inflammation and damage are the main drivers of cardiovascular risk/disease. Endothelial repair is mediated in part by recruitment of bone marrow endothelial progenitor/endothelial colony forming cells (EPC/ECFC). People with HIV (PWH) have increased cardiovascular risk and the impact of infection in endothelial repair is not well defined. The low frequencies and challenges to in vitro isolation and differentiation of EPC/ECFC from PBMCs had made it difficult to study their role in this context. We hypothesized that HIV driven inflammation induces phenotypic changes that reflects the impact of infection. To test this hypothesis, we evaluated expression of markers of trafficking, endothelial differentiation, and angiogenesis, and study their association with biomarkers of inflammation in a cohort of PWH. In addition, we investigated the relationship of circulating endothelial progenitors and angiogenic T cells, a T cell subset with angiogenic function. Using a flow cytometry approach, we identified two subsets of circulating progenitors LIN4-CD45-CD34+ and LIN4-CD45dimCD34+ in PWH. We found that the phenotype but not frequencies were associated with biomarkers of inflammation. In addition, the percentage of LIN4-CD45dimCD34+ was associated with serum levels of lipids. This data may provide a new tool to better address the impact of HIV infection in endothelial inflammation and repair.